The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.omtn.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Novel Single-Stranded RNAi Agent Targeting Periostin in Eyes with Retinal Neovascularization

Abstract: Retinal neovascularization (NV) due to retinal ischemia remains one of the principal causes of vision impairment in patients with ischemic retinal diseases. We recently reported that periostin (POSTN) may play a role in the development of preretinal fibrovascular membranes, but its role in retinal NV has not been determined. The purpose of this study was to examine the expression of POSTN in the ischemic retinas of a mouse model of oxygen-induced retinal NV. We also studied the function of POSTN on retinal NV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…IL-13 is an important type 2 T helper (Th2) cytokine controlling biological functions in tissue remodeling such as angiogenesis and fibrosis [34][35][36][37] . We previously found IL-13 up-regulation in the vitreous humors of PDR patients and OIR mice retinas, which suggests that ischemic injury induces IL-13 expression and secretion in the retina 19,31 . Meanwhile, after central nervous system (CNS) injury by stroke, a shift towards Th2 response and downregulation of Th1 response play a role in tissue remodeling during CNS wound healing response 38 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…IL-13 is an important type 2 T helper (Th2) cytokine controlling biological functions in tissue remodeling such as angiogenesis and fibrosis [34][35][36][37] . We previously found IL-13 up-regulation in the vitreous humors of PDR patients and OIR mice retinas, which suggests that ischemic injury induces IL-13 expression and secretion in the retina 19,31 . Meanwhile, after central nervous system (CNS) injury by stroke, a shift towards Th2 response and downregulation of Th1 response play a role in tissue remodeling during CNS wound healing response 38 .…”
Section: Discussionmentioning
confidence: 90%
“…Our group subsequently demonstrated that PN and TNC were highly up-regulated in the vitreous humor of patients with PDR and proliferative vitreoretinopathy, and promoted both retinal angiogenesis and fibrosis in the pathogenesis of vitreoretinal diseases [17][18][19][20] . Accumulated evidence suggest that ECM components including PN, TNC and fibronectin (FN) that is a well-characterized molecule, promotes physiological and pathological retinal angiogenesis [21][22][23][24][25][26] .…”
mentioning
confidence: 99%
“…We found that BLT1 + cells infiltrated into the periphery of the macular drusen, a common early sign of AMD, and choroidal capillaries in the RPE-choroid of diabetic human eyes but not in nondiabetic human eyes. Recent studies show that infiltrated macrophages exhibit M2-phenotype, which accelerate neovascularization to promote tissue repair in the injured retina of retinopathy (38,79,89,90). Hence, the BLT1 may be a promising therapeutic target for CNV of several diseases, including wet AMD.…”
Section: Discussionmentioning
confidence: 99%
“…This gap increases bleeding and causes hyperplasia and pathological changes, which leads to irreversible damage to the structure and function of the eye, ultimately resulting in a serious decline in vision and potentially blindness. Keratitis is a common eye disorder that often leads to the formation of new blood vessels ( 5 , 6 ). Paxillin (PXN) is a focal adhesion protein, and is comprised of an LD motif (containing the consensus peptide sequence LDXLLXXL), a conserved cysteine-rich domain comprising of ~60 amino acids with seven conserved cysteine residues and a histidine residue (LIM domain), Src homology 2 (SH2) domain and Src homology 3 (SH3) domains ( 7 ).…”
Section: Introductionmentioning
confidence: 99%